Enhancing Learning Interest in Mathematics: Integrating Problem-Based Learning with a Kinesthetic Game and Music - Desy Cahyani; Nevrita Nevrita; Encik Abdulhajar; Tety Kurmalasari (Yayasan Sembilan Pemuda Indonesia, 2026)
This study was motivated by the low level of learning interest in mathematics among tenth-grade students and aimed to analyze the effect of integrating Problem-Based Learning (PBL) with the kinesthetic game Walking Marker, accompanied by music, on students’ interest in learning mathematics. The research employed a quasi-experimental design with a non-equivalent control group design. The participants consisted of 64 tenth-grade students from SMA Negeri 1 Bintan Timur, who were divided into an experimental group (n = 32) and a control group (n = 32). The experimental group received PBL instruction integrated with a kinesthetic game and music, while the control group was taught using conventional PBL. Students’ learning interest was measured using a validated learning interest questionnaire administered before and after the intervention. Data analysis included tests of normality, homogeneity, and an independent samples t-test. The results indicated that integrating the Problem-Based Learning (PBL) model with the kinesthetic game Walking Marker, accompanied by music, significantly enhanced students’ interest in learning mathematics. This finding was supported by the results of the independent samples t-test, which revealed a significant difference between the experimental and control groups, t(62) = 9.920, p < .001, with a mean difference of 11.03 points and a large effect size (Cohen’s d = 1.18). This study offers novelty through the integration of PBL, a kinesthetic game, and music as an effective multimodal approach to increasing students’ interest in learning mathematics and provides practical implications for teachers in designing more engaging and meaningful learning experiences. Furthermore, this study contributes empirical evidence regarding the effectiveness and magnitude of the impact of a multimodal PBL approach on students’ learning interest in mathematics education.